Pro Environmental Behavior: Is the Travelers Apply It in The City of Denpasar? - Gde Bagus Brahma Putra; Made Santana Putra Adiyadnya; Ni Putu Yuria Mendra (International Journal of Tourism and Hospitality in Asia Pasific, 2019)
This study aims to investigate whether energy conservation, mobility and transportation, waste avoidance, recycling, consumerism, and vicarious behaviors toward conservation play a role in the formation of pro-environmental behavior among tourists visiting sites in the city of Denpasar. The results showed that the six of behaviors that forming pro environmental behavior, two of them were not had an influence on the formation of pro environmental behavior among the tourists visiting the historical sites in the city Denpasar. Such behavior is Energy conservation, and Mobility and transportation. Keywords: pro environmental behavior, energy conservation, mobility, behavior, tourism